PREFERENSI KONSUMEN PADA CITRA FASHION - Rahmadianti, Yola; Wesnina, Wesnina; Zahra, E Lutfia (Practice of Fashion and Textile Education Journal, 2023)
This study aims to obtain information about consumer preferences on fashion imagery in fast fashion brands and local clothing brands. The research method uses a survey method with a descriptive quantitative approach. This research instrument is in the form of a questionnaire with a research sample of 100 male and female respondents aged 18- 25 years who live in DKI Jakarta using Google Form on a research sample of 100 respondents with a likert scale. The results of this study show indicators of personality, credibility, attributes, social status, guarantees and benefits in the variables of consumer preferences on the image of fashion show well. The highest percentage obtained from the social status indicator of 73% indicates good which means that generation Z has a brand image preference that can create a social status such as looking fashionable in order to be recognized by peer groups. The lowest percentage obtained by the credibility aspect, namely 58% shows good, which means that generation Z has a credibility preference that presents products according to advertisements and trusted quality.